Calculated plasma volume status is associated with poor outcomes in acute ischemic stroke treated with endovascular treatment - Zhang, Dixia; Li, Qiuru; Liu, Jun; Ma, Lijuan; Ye, Jing; Hu, Guifen; Li, Guangzong (Frontiers in Neurology, 2023)
Background and purpose: The impact of calculated plasma volume status (PVS) on prognosis in acute ischemic stroke treated with endovascular treatment (EVT) remains undetermined. This study aimed to investigate the association between PVS and 90 days functional outcomes after EVT.We enrolled patients treated with EVT in the anterior circulation from a prospective registry. The end point was a modified Rankin scale score ≥3 points at 90 days after EVT. We used multivariable logistic regression models to investigate the association between PVS and poor outcomes. We used the restricted cubic spline to present the linearity between PVS and poor outcomes.Results: Among the 187 enrolled patients (median age, 65 years; 35.8% female), a total of 81 (43.3%) patients experienced poor outcomes at 90 days. In multivariable analyses, PVS was associated with poor outcome despite increasing confounding factors (odds ratio, 3.157; 95% confidence interval, 1.942-5.534; P < 0.001). The restricted cubic spline revealed a positive correlation between PVS and the risk of poor outcomes after EVT (P for nonlinearity = 0.021).Our study found that elevated PVS value was associated with poor outcomes after EVT. Further prospective cohorts were warranted to evaluate the utility of PVS in AIS treated with EVT.